A decade of corruption studies in Malaysia. Issue 2 (3rd February 2020) - Muhamad, Nurisyal; A. Gani, Norhaninah
Abstract : Purpose: In December 2013, the World Bank had declared that, in the developing world, corruption is the No.1 public enemy. True, Malaysia has been swayed by the endless corruption scandals from the upper classes to the subordinates, in public as well as private sectors. As a country that is moving towards being a developed country in 2025, the Malaysian Government has been working hard to overcome corruption through various plans and initiatives. Thus, the purpose of this paper is to highlight on Malaysia's current initiatives and factors that had been found to be of significant importance by previous studies for combating corruption in Malaysia. Design/methodology/approach: This study employed structured review process as well as critically examined the contents to ensure that the data are filtered from high-quality peer-reviewed journals. Twenty-five quality papers were selected from top journals of various areas to produce the list. Findings: This paper contributes to the existing literature by providing a comprehensive list of factors in Malaysia in the fight against corruption. Originality/value: This study will be beneficial to academics, policymakers and anti-corruption professionals interested in Malaysia's anti-corruption experiences.